2007
DOI: 10.4038/jnsfsr.v35i2.3675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late planting heat stress on membrane thermostability, proline content and heat susceptibility index of different wheat cultivars

Abstract: Four wheat cultivars e.g., Aghrani, Kanchan, CB-30 and Sonora were tested under normal and post anthesis heat stress condition by seeding them on November 30 and December 30 to evaluate the heat tolerance of wheat in relation to proline content. Time to exceed 50% membrane leakage was about four times longer in Aghrani, and the cultivars were grouped as heat tolerant (HT) than in Sonora (30 min) which considered as heat sensitive (HS). Due to post anthesis heat stress condition the HS cultivar Sonora in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
4
15
0
1
Order By: Relevance
“…Thus it indicated the importance of harvesting the crop and quickly drying the wheat grains when it attain at physiological maturity. Similar pattern of spike dry matter accumulation in wheat was also found by Hasan et al (2007) (Table 4). In water deficit stress, plant suffers from physical drought and consequently the reduction in plant height was observed.…”
Section: Physiological Traits Physiological Traits Physiological Traisupporting
confidence: 84%
“…Thus it indicated the importance of harvesting the crop and quickly drying the wheat grains when it attain at physiological maturity. Similar pattern of spike dry matter accumulation in wheat was also found by Hasan et al (2007) (Table 4). In water deficit stress, plant suffers from physical drought and consequently the reduction in plant height was observed.…”
Section: Physiological Traits Physiological Traits Physiological Traisupporting
confidence: 84%
“…Proline content (μ moles/g/fresh weight) was determined according to the method of (Bates, et al, 1973), and expressed on a fresh weight basis from the standard curve, using standard L-Proline according to the previous method developed (Hasan, et al, 2007). However, the Proline content was determined from a standard curve and calculated on a fresh weight basis as follows : µmoles Proline/g of fresh plant material = [(µg Proline/ml × ml toluene)/115.5 µg/µmoles / (g sample/5)] as reported by Ahmed and Hasan (2011).…”
Section: Experiments 1: Divided Into 3 Portionsmentioning
confidence: 99%
“…Under high temperature, free proline is involved in osmotic adjustment to protect pollen and plant enzymes from heat injury, and also provides a source of nitrogen and other metabolites (VERSLUES and SHARMA 2010). Accumulation of proline has been shown to occur under heat stress in arabidopsis (WEI-TAO et al 2011), cotton (RONDE et al 2001) and wheat (HASAN et al 2007), and genotypic variation in proline accumulation have been reported for these species. Under high temperature certain heat shock genes are triggered, resulting in the synthesis of heat shock proteins, whereas other soluble and insoluble proteins have also been shown to exhibit changes in abundance under high temperature stress (SIMMONDS 1995, HE et al 2005.…”
Section: Introductionmentioning
confidence: 99%